A retrospective audit of the use of fresh frozen plasma at a tertiary care hospital - Gounden, Reenelle (My University, 2019)
Background: Blood transfusions reduce morbidity and mortality in hospitalized patients. Fresh Frozen Plasma (FFP) is one of the most commonly used blood products in many clinical settings as well as the one least understood in its indications for use. While guidelines on the use of FFP have been published by the South African National Blood Service (SANBS), there is a paucity of data on how well these are followed. Objectives: This study assessed the indications and appropriate use of FFPs in a tertiary care hospital. Method: A retrospective audit was conducted over six months from March to August 2015 at the CMJAH. The study was reviewed and approved by the University of the Witwatersrand and SANBS Human Research Ethics Committees. Study participants included all recipients of FFP at the CMJAH during the study period. Data on indications for FFP, volumes of FFPs transfused, clinical units transfusing the FFPs, were collected and analysed. Results: There was a total of 1233 FFP transfusions to 736 patients during this study period. 53.8% of these transfusions were appropriate following the SANBS blood transfusion guidelines while 39.4% were inappropriately transfused and a further 6.8% of FFP transfusions were indeterminate. The appropriate indications for FFP transfusions included multiple factor deficiencies, reversal of warfarin and thrombotic thrombocytopenic purpura. The inappropriate indications involved; bleeding without a coagulopathy, abnormal coagulation studies in a non-bleeding patient and prophylactic use before invasive procedures. Conclusion: In this retrospective audit, half FFP transfusions were appropriate while 40% were inappropriate according to current guidelines. This study highlights the need for education on the use of FFP in our institution.
A research report (in the format of a “submissible” paper) submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Medicine (Haematology) Johannesburg, 2019
Keywords: Plasma; Blood Coagulation; Blood Transfusion